Dampak Pembelajaran Daring Terhadap Putusnya Sekolah di MTs Ma'arif Bakalan Desa Bowongso - Salis Irvan Fuadi; M. Nurul Hilal Awwaly; Etika Sari; Eva Ainur; Fitri Yunita; M. Shofi Burhanus; Desta Akhmad Ramadhani; Suli Anggita Nurul Izami; Dessy Putri Herawati; Yoga Praticta; Jihan Muntiza (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2022)
The impact of the COVID-19 pandemic has affected all aspects of the economy, social, and education. Education is the most highlighted thing, because the teaching and learning system that should be done face-to-face must be done online or online according to government policy. The government policy requires every student to have a mobile phone to be able to take part in online learning (in the network). During the COVID-19 pandemic, teaching and learning activities at MTs Ma'arif Bakalan were carried out online or online, so students were sent home. Within a period of 2 (two) months online teaching and learning activities at MTs Ma'arif Bakalan caused as many as 12 (twelve) students at MTs Ma'arif Bakalan to drop out of school. Through this article, we will examine in depth the causes or other things related to the impact of online learning on school dropouts at MTs Ma'arif Bakalan.